Design of Android-Based Card Production Scheduling System Application using Rapid Application Development Method - Barokah, Irma; Azrino Gustalika, Muhamad (INOVTEK Polbeng - Seri Informatika, 2025)
PT. Cazh Teknologi Inovasi is a company focused on delivering excellent customer service. However, the current card production scheduling process, which is still managed manually through social media, has led to several issues, including a high risk of human error, product backlog, and long customer waiting times. These problems negatively impact service quality and customer satisfaction. To address this, an Android-based card production scheduling system was developed using the Rapid Application Development (RAD) method, which enables fast and flexible application development tailored to the company's needs. The system was tested using the black box method to ensure that each feature functions according to its specifications. The test results indicate that the system is feasible for use and can improve production efficiency while reducing customer waiting time.